The Effect Of Job Satisfaction, Work Motivation, Work Placement And Work Ethic On The Work Performance Of Employees Of The Agriculture Service Of Empat Lawang District - Hadi Hermanto; Nisma Aprini; Delvina Yulanda (Utami Publisher, 2026)
The purpose of this study is to determine and analyze the influence of job satisfaction, work motivation, job placement and work ethic both individually and collectively on the work performance of employees of the Agricultural Service of Empat Lawang Regency. The research method used in this study is a quantitative method using a questionnaire distributed to respondents. Data quality testing using validity tests, reliability tests and normality tests. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial tests, simultaneous tests and coefficients of determination. The results of the study obtained job satisfaction significantly influence the work performance of employees of the Agricultural Service of Empat Lawang Regency. Work motivation significantly influence the work performance of employees of the Agricultural Service of Empat Lawang Regency. Job placement significantly influence the work performance of employees of the Agricultural Service of Empat Lawang Regency. Work ethic significantly influence the work performance of employees of the Agricultural Service of Empat Lawang Regency. Job satisfaction, work motivation, job placement and work ethic significantly influence the work performance of employees of the Agricultural Service of Empat Lawang Regency.